LAND GOVERNANCE; FACTS AND EFFECTS. CASE OF THE CITY OF TAHER (WILAYA OF JIJEL IN EASTERN ALGERIA) - Bougassa Abdelhafid, (International Journal of Innovative Technologies in Social Science, 2024)
All religious laws and man-made laws call for the preservation and sustainability of natural resources, including land as an irreplaceable element.Compliance of land use with the guidelines of development and town planning instruments is a basic principle in land use. This rule of good governance leads to the protection of the environment, natural resources and the preservation of the natural, cultural and socio-economic heritage marking a given territory. Aware of this reality, the Algerian state anticipated this problem early on through the promulgation of laws and regulations governing territorial management, the occupation of urban land and the protection of the environment within the framework of sustainable development.However, the divide between land allocations and its use on the scale of certain urban areas on the eastern outskirts of the city of Jijel gives food for thought on the reliability and feasibility of urban planning instruments in the control of land management. . This deficiency is manifested by the disorderly extension of the built environment, the consumption of natural, forest and agricultural space. This trend, accompanied by the increase in population, generates increasing needs for equipment and amenities and difficulties in the management of all types of waste produced.Taking the case of the city of Taher as a study framework, the decadence of heritage wealth (social way of life, agricultural activities, low population and construction density, hygiene and environmental balance) can increase on board be noticed in view of the areas withdrawn annually from natural landscapes and agriculture. In order to control urbanization and meet the needs for individual housing, the municipality of Taher has planned several subdivisions in accordance with the town planning plan. Despite the fact that the majority of designated land bases are of a public legal nature, these operations for individual residential use have been abandoned under the effect of constraints and disputes. As a result, the land areas in question are invaded by constructions which do not necessarily meet town planning standards and land use rules.